Pengembangan Lms Berbasis Moodle Dengan Model Pjbl Untuk Meningkatkan Kemampuan Kognitif Pada Elemen Pemrograman Web Kelas 11 Tkj Smkn 1 Surabaya - Fauzan Ainur Rofiq; Muhammad Sonhaji Akbar (CV. SINAR HOWUHOWU, 2026)
Learning in the Web Programming element for Grade 11 Computer and Network Engineering (TKJ) students at SMKN 1 Surabaya still faces challenges, including limited utilization of the Learning Management System (LMS), teacher-centered instruction, and students' cognitive abilities that have not reached the expected level. This study aimed to develop a Moodle-based Learning Management System integrated with the Project-Based Learning (PjBL) model, evaluate its feasibility, and examine its effectiveness in improving students' cognitive abilities. This study employed the Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation. The research involved Grade 11 TKJ students at SMKN 1 Surabaya, divided into an experimental class and a control class. Data were collected through expert validation, tests, observations, interviews, documentation, and Black Box Testing. The collected data were analyzed using the Shapiro–Wilk normality test, Levene's homogeneity test, and the Mann–Whitney U test. The results showed that the developed LMS was highly valid, with validation scores of 97.39% for the teaching module, 90.00% for the media, 91.81% for the learning materials, and 95.00% for the test instruments. Black Box Testing confirmed that all LMS features functioned as intended. The experimental class achieved a higher average posttest score (88.33) than the control class (78.66), while the average pretest scores were 61.50 and 64.00, respectively. The Mann–Whitney U test produced a significance value of p < 0.001, indicating a significant difference between the two groups. Therefore, the Moodle-based LMS integrated with the PjBL model is feasible for implementation and effective in improving students' cognitive abilities in the Web Programming element.